(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The shifting employer-employee dynamics have helped in new trends like the ‘great resignation’ and the ‘upskilling imperative’, that are driving talent management priorities today in ICT Companies in India. Today’s talent wants to be continuously connected and engaged. Typically, the talent management process tends to focus on the identification of High Potential and their Development and Succession Planning. HONO’s suite of solutions - “enable, engage, and transform”, covers the entire spectrum of managing talent – right from acquiring the right talent, on boarding, engaging, retaining, developing and grooming them to be winning leaders in ICT Companies. Over the past two years, in ICT Companies the HR leaders and practitioners have had to unlearn and find new ways to reinvent the talent management wheel. They had to tap into the right blend of low-touch and high-tech processes to engage and develop talent.